Verruciform xanthoma of the vulva in the context of lichen sclerosus: A mimicker of HPV and p53-independent intraepithelial neoplasia - Simon F. Roy; Jahg Wong; Kurosh Rahimi (Elsevier, 2021)
A 67-year-old woman presented with a 2 x 1.5 cm white, asymptomatic verrucous plaque on the left labia minora. She was known for vulvar lichen sclerosus et atrophicus (LSA) for 1.5 years, treated with high-potency topical corticosteroids. A biopsy of the verrucous lesion demonstrated a small fragment of parakeratotic vulvar epithelium with papillomatosis and moderate basal atypia, spongiosis and mitoses. Neutrophils were present, forming microabscesses in the stratum corneum. The granular layer was lost in those acanthotic areas. The differential diagnosis included vulvar verruciform lichen simplex chronicus, verrucous carcinoma, vulvar acanthosis with altered differentiation, differentiated exophytic vulvar intraepithelial neoplasia or verruciform xanthoma. We demonstrate how accurately diagnosing verruciform xanthoma in the context of inflammatory dermatoses of genital sites is crucial to avoid overtreating as a preneoplastic mimicker lesion.